-9(z-97)=45

Simple and best practice solution for -9(z-97)=45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(z-97)=45 equation:


Simplifying
-9(z + -97) = 45

Reorder the terms:
-9(-97 + z) = 45
(-97 * -9 + z * -9) = 45
(873 + -9z) = 45

Solving
873 + -9z = 45

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-873' to each side of the equation.
873 + -873 + -9z = 45 + -873

Combine like terms: 873 + -873 = 0
0 + -9z = 45 + -873
-9z = 45 + -873

Combine like terms: 45 + -873 = -828
-9z = -828

Divide each side by '-9'.
z = 92

Simplifying
z = 92

See similar equations:

| 8=7z-(3-9z)-2z | | 210=-3(-6+8x) | | X-12+1x=180 | | 1.25x-.45y=200 | | 6f-21=39 | | 4(3-4r)=124 | | 80=5(s-99) | | b/6-3 | | 1/3n-- | | %488=610 | | -178=-7(1+7v)-8v | | 400x^2+4x-9=0 | | 2(8d-9)=-20 | | 23.95+x=26.95 | | 7x+159+c=180 | | 9/4=x/7.5 | | (8/(5x-45))-(3/(2x-18)) | | f(2.5)=2x^2-3x+7 | | 45+(-39)= | | 5k+7-3=35 | | 6x+2(.5)=5 | | 13y+13=4y+2 | | 13x+13=4y+2 | | 8f-93=27 | | x^2-4x+y^2+2y-5=0 | | -183=1+8(1-6n) | | 2y+1=4x+17 | | t^2-48t+576=0 | | 7x=1/2401 | | 11=-d+75 | | 15.07+x=27.05 | | 1.042=x-x^2 |

Equations solver categories